Assessing the impact of hand hygiene training on medical students’ knowledge: A study in a tertiary care hospital in West Bengal. - Tapajyoti Mukherjee; Purbasha Ghosh; Arindam Dasgupta; Soumi Nag; Syeda Azra Zabin; Minakshi Das (International Journal of Endorsing Health Science Research, 2023)
Background: Healthcare-associated infections (HAIs) continue to pose significant challenges to patient safety and healthcare systems worldwide. Poor hand hygiene among healthcare professionals remains a major contributing factor to the spread of HAIs. Despite its importance, hand hygiene compliance among healthcare workers, including medical students, remains low. Training programs to improve hand hygiene knowledge and compliance have been implemented globally. This study aimed to assess the impact of a hand hygiene training program on medical students at Burdwan Medical College & Hospital in West Bengal. Methodology: A cross-sectional study was conducted involving 122 Professional MBBS students who were selected through purposive sampling. Written informed consent was obtained from each participant. The students' baseline hand hygiene knowledge was assessed using the WHO questionnaire before providing hand hygiene training. Post-training, the same questionnaire was used to evaluate the level of knowledge acquired. The data were analyzed using the student t-test to determine the statistical significance of the training program. Results: The mean pre-test score was 11.24±5.29, while the mean post-test score significantly increased to 17.34±5.4 (p<0.001, 95% CI). This finding indicates a substantial improvement in hand hygiene knowledge among medical students after undergoing the training program. Conclusion: Regular and frequent training programs on hand hygiene, accompanied by monitoring and timely feedback, are crucial for increasing awareness and compliance among medical students. It is essential for medical colleges to establish an Infection Prevention and Control Committee to organize and oversee such training initiatives, which play a pivotal role in mitigating the risk of HAIs.